Performa Benih Kakap Putih (Lates calcarifer) yang Diberi Pakan Kombinasi Maggot (Hermetia illucens) dan Pakan Komersil - Marisya Apriyanti; Supono Supono; Munti Sarida (Journal of Tropical Marine Science, 2023)
Feed is the main thing needed in the cultivation of Asian seabass seeds. An appropriate composition of fish feed ingredients affect the growth, development, and survival rate of this Asian seabass seeds. This study aims to analyze the effect of the combination of maggot and artificial feed (pellets) on the growth, survival, feed conversion, and efficiency of feed utilization of Asian seabass (Lates calcarifer) seeds. The study was conducted for 30 days, using a completely randomized design with 4 treatments and 3 replications, namely: treatment A (feeding pellets 100%), B (feeding pellets 75% and maggot 25%), C (feeding pellets 50% and maggot 50%), D (25% pellet feed and 75% maggot) with a feeding rate (FR) of 7% of fish body weight. The data that has been collected were analyzed using Analysis of Variance (ANOVA) at a 95% confidence level with SPSS software. If the treatment had a significant effect, further tests would be carried out using the Tukey test. The results show that the combination of maggot and pellets affects the growth, survival, feed conversion, and efficiency of feed utilization of Asian seabass seeds. The best combination is 75% for maggots and 25% for pellets.